Tralokinumab for the treatment of severe, uncontrolled asthma: the ATMOSPHERE clinical development program. (14th March 2018) - Panettieri Jr, Reynold A; Wang, Millie; Braddock, Martin; Bowen, Karin; Colice, Gene
Tralokinumab, a fully human IgG4 monoclonal antibody, specifically neutralizes IL-13. The ATMOSPHERE clinical development program comprised four randomized, placebo-controlled clinical trials and an open-label study that aimed to assess the efficacy and safety of tralokinumab for the treatment of severe, uncontrolled asthma. The two pivotal trials (STRATOS 1 and STRATOS 2; NCT02161757 and NCT02194699) evaluated the efficacy and safety of tralokinumab, with STRATOS 1 identifying a subgroup most likely to demonstrate enhanced response to treatment. Further trials have assessed the ability of tralokinumab to reduce oral corticosteroid use (TROPOS; NCT02281357) and determined its mechanistic effects (MESOS; NCT02449473). An open-label study in Japanese individuals (NCT02902809) assessed the long-term safety and tolerability of tralokinumab in this population.